SWOT Analysis to Explore the Development of Smart Retail Vending Machines in the Countryside - Wang, Peng; Chen, Weiqiang (International Journal of Social Sciences and Public Administration, 2024)
With the rapid development of rural economy and the improvement of residents’ living standards, smart retail vending machines have shown great potential in the rural market. As an emerging retail model, rural smart retail vending machine combines modern information technology and intelligent hardware, aiming to improve the retail service level in rural areas. In this paper, the strengths, weaknesses, opportunities and threats of rural smart retail vending machines are systematically explored using SWOT analysis to assess their development prospects and challenges in the rural market. Smart retail vending machines can provide round-the-clock services and enhance the convenience of access to goods and shopping experience in rural areas. Meanwhile, the vending machines are able to achieve accurate inventory management and personalized product recommendation through intelligent management and data analysis, thus improving operational efficiency. Rural smart retail vending machines have significant development potential, but in the process of promotion, it is necessary to pay attention to the investment cost, technical maintenance, and market acceptance in order to realize its wide application and long-term development in rural areas.